[PP.11.04] OSCILLOMETRIC METHOD IDENTIFIES SUBCLINICAL ATHEROSCLEROSIS EVEN WHEN MILD DECREASE OF ANKLE-BRACHIAL INDEX. (September 2016) - Ameijeiras, A. Hermida; Paz, J.E. Lopez; Alende, M.J.; Montes, A. Pascual; Durán, V. Martínez; González, G. Calvo; Lado, F.L. Lado; Gomez, C. Calvo
Abstract : Objective: Low ankle brachial index (ABI) ratios (< 0.9) predict higher risk of cardiovascular events. Subjects with an ABI between 0.91 and 1.00 are considered "borderline" in terms of cardiovascular risk and further evaluation is appropriate. The aim of this study was to assess the validity of the oscilometric method to detect subclinical atherosclerosis in those subjects with mild decrease of ABI. Design and method: A cross sectional study was conducted among 328 hypertensive subjects (46.6% women). Patients underwent a ultrasonography study (Sonosite M-Turbo™. SonoCalc IMT®) to evaluate carotid intima-media thickness (IMT) and oscillometric method (Microlife Watch BP Office ABI) to assess ankle-brachial index (ABI). Subjects were classified according to ABI ratio into four different groups: low (< 0.9); mild-low (0.9–0.99). normal (1–1.4) or over 1.4. Results: Low ABI was detected in 8.5%. mild-low ABI in 30 subjects (9.1%). 262 subjects were normal (79.8%) and only 8 were ABI > 1.4 (2.4%). We observed differences between groups according to waist circumference (105.2 Vs 101.6 Vs 101.4 Vs 99.5 cms, respectively). There were no differences between groups according to weight or BMI. When comparing those subjects with normal ABI and mild-low ABI we only found differences on DBP (85.14 Vs 81.53 mmHg) and pulse pressure (58.68 Vs 65.63 mmHg). Regarding IMT. mean values were 0.9 mms (ABI < 0.9); 0.87 mms (ABI 0.91- 0.99). 0.8 mms (normal ABI) and 0.73 mms (ABI > 1.4). Distribution of abnormal IMT values (> 0.9 mms) were detected in 47% Vs 44% Vs 23% Vs 0%, respectively. ABI correlated poorly and inversely with IMT (r: −0.136; CI 95%:0.02 – 2.28; p = 0.018). Conclusions: Even with mild-low ABI levels (between 0.9 and 0.99) double chance of detect subclinical atherosclerosis assessed by IMT estimation. Oscilometric method provides an accuracy, reliable and easy method to determine subclinical atherosclerosis even in those subjects with mild-low ABI.